Resignation as one of the reasons for the employee's termination of service in light of the Jordanian civil service system and the Algerian public service law - Abu Rashed, Hitaf Jumah (Journal of Economic, Administrative and Legal Sciences, 2022)
This study dealt with a statement of the provisions of resignation as one of the reasons for the employee’s termination in light of the Jordanian civil service system for the year 2020, and the Algerian public service law for the year 2006. The explicit, considering this to be the type adopted by the legislator in Jordan and Algeria. The study dealt with the conditions and controls of resignation in terms of the requirement: the written request and the explicit will, the absence of the request from conditions or restrictions, the extent of the administration’s right to accept or reject the resignation request, and the prohibition of accepting the resignation when the employee is in organizational and legal conditions that are inappropriate to accept it, such as being subject to discipline or Committed to serving for a certain period of time for a currency authority, and the necessity of him continuing to perform his work duties until the approval of the administration, explicit or implicit, is issued. The study also exposed the effects of the resignation, including: the end of the legal bond between the employee and the job, his loss of the financial rights that he was receiving while at the head of his job, his right to an end-of-service gratuity or the addition of his approved years of service to the retirement pension, his right to be re-appointed to the job, and his continued commitment to maintaining On the secrets of work until they are no longer considered confidential, and discussing the position of the legislator in the two countries on these issues and elements, and drawing on jurisprudential opinions in this regard. Weaknesses and shortcomings here or there, as is the case with research studies, and the study found some scenarios that hoped for the positive impact of functional legislation in both Jordan and Algeria.
Keywords: Resignation; public servant